Social enterprises, job creation, and social open innovation - Ji Hee Park; Cheol Young Kim (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
How can social problems be solved? The complicated and rapidly changing problems of modern society require all the actors of the economy to create social values to solve problems. Social enterprises create social value in the field of business and solve many social problems through employment. The increasing number of diverse social problems has stimulated interest in social enterprises. This study identifies employment in social enterprises in terms of its quantity and quality. The human resources required for social enterprises must be unique and valuable, but many social enterprises fail to utilize human resources by maintaining contractual and short-term employment relationships even though long-term and continuing employment relationships are valuable. Therefore, this study identifies the economic value created by social enterprises as a basis for the creation of high-quality jobs and confirms the role that government grants and return on assets play in that relationship. As a result of panel analysis of social enterprises, the direct effect of net income on the quantity of employment and its indirect effect on the quality of employment were confirmed. Additionally, in companies receiving significant government grants, the relationship between net income and the quantity of employment is found to be strong, and the return on assets found to strengthen the indirect effects of net income on the quality of employment. This study has academic and practical implications for social enterprises through its review of theory and empirical analysis.
Keywords: 650; employment; governmental grant; net income; pay level; social enterprise